80/20 triathlon discover the breakthrough elite-training formula for ultimate fitness and performance at all levels - Fitzgerald, Matt; Warden, David 1974- (New York, NY Da Capo, LIFE LONG, 2018)
"Cutting-edge research has proven that triathletes and other endurance athletes experience their greatest performance when they do 80 percent of their training at low intensity and the remaining 20 percent at moderate to high intensity. But the vast majority of recreational triathletes are caught in the so-called "moderate-intensity rut," spending almost half of their time training too hard--harder than the pros. Training harder isn't smarter; it actually results in low-grade chronic fatigue that prevents recreational athletes from getting the best results. In 80/20 Triathlon, Matt Fitzgerald and David Warden lay out the real-world and scientific evidence, offering concrete tips and strategies, along with complete training plans for every distance--Sprint, Olympic, Half-Ironman, and Ironman--to help athletes implement the 80/20 rule of intensity balance. Benefits include reduced fatigue and injury risk, improved fitness, increased motivation, and better race results"--
The most effective way to train -- Going slower to get faster -- The science of 80/20 training -- Swimming the 80/20 way -- Cycling the 80/20 way -- Running the 80/20 way -- Strength, flexibility, and mobility training -- Getting started with 80/20 training -- Introduction to 80/20 training plans -- 80/20 triathlon training plans: sprint distance -- 80/20 triathlon training plans: olympic distance -- 80/20 triathlon training plans: half ironman distance -- 80/20 triathlon training plans: ironman distance -- 80/20 triathlon training plans: maintenance -- Race day.
Includes index.
Foreword by Stephen Seiler.
Keywords: Triathlon -- Training